Islam, Science and Society - Gamaryani, Yahya Ashraf (sourcecoder, 2024)
Islam is a complete code of life and a religion of nature that takes into account all the conditions and changes related to the external and internal existence of man and the universe. And he looks at all these conditions and changes. It is an indisputable fact that Islam provided the foundations of modern science by enlightening humanity wandering around Greek philosophy. The main theme of the Qur'an is "man", who is called many times to be aware of the happenings and events of the world around him. Reflect, reflect, act, and use the powers of awareness and observation that have been given to you. It should be noted that the Qur'an and Sunnah do not explain science and technology issues in detail, but the order for a Muslim is to think about Allah's creation, acquire knowledge, and discuss and use worldly facts. The conclusion is that the Qur'an is a book that encourages prudence. Presents narratives about nature and science that inspire and satisfy the audience, whether they belong to the 14th century or the 7th century, or today, it makes the reader think that this book How would the author of It is the duty of Islamic scholars to understand the contemporary scientific issues related to Islam, science, and society in a timely manner and to guide the Ummah and humanity in the light of the Qur'an and Sunnah. To clarify, this article is also a small effort in this regard. May Allah be our supporter and supporter.